Assessment on Aspects of Artificial Intelligence in Public Policy and Decision-making Process - Putri, Primaristianti; Mayasari, Ima (Syntax Corporation, 2024)
The development and use of Artificial Intelligence (AI) has become a widely discussed topic, not only in Indonesia but also globally. The emergence of ChatGPT in 2022 has led to the rapid development and use of AI in various fields, such as medicine, creative industries, academics, and social entrepreneurship. The history of AI development began with the creation of the Enigma code-breaking machine during World War II by Alan Turing. Since then, AI research has continued to evolve, with the Turing Test serving as the basis for identifying the intelligence of an artificial system. The COVID-19 pandemic has also accelerated the development of AI, particularly in the use of big data for diagnosis. The introduction of ChatGPT, a generative AI program, has further increased public interest in AI. The capability of AI to process vast amounts of data give the opportunity to help public administrators in data analysis for policy-making. The government can utilize AI to assist the government in each stage of the policy process. However, as AI technology continues developing, AI still poses some challenges that need to be addressed before its implementation. The government also needs to ensure its preparedness in both infrastructure and organization before fully utilizing the potential of AI technology in policy-making.